Ida - Evans, Alison, (Zine creator) (Richmond, Victoria : Echo, 2017)
How do people decide on a path, and find the drive to pursue what they want? Ida struggles more than other twenty-somethings to work this out. She can shift between parallel universes, allowing her to follow alternative paths. One day Ida sees a shadowy, see-through doppelganger of herself on the train. She starts to wonder if she's actually in control of her ability, and whether there are effects far beyond what she's considered. How can she know, anyway, whether one universe is ultimately better than another? And what if the continual shifting causes her to lose what is most important to her, just as she's discovering what that is, and she can never find her way back?
14+.
Victorian Premier's Literary Award, People’s Choice Award, winner, 2018.
Keywords: Doppelgängers -- Fiction; Doppelgängers -- Juvenile fiction; Choice -- Juvenile fiction; Space and time -- Juvenile fiction; Australian fiction; Young adult fiction; Science fiction; Science fiction; Australian; Paranormal fiction; Young adult fiction